Quality of Chaetoceros calcitrans Cultured with Different Concentrations of Potassium Nitrate (KNO3) - Prafanda, Alfarisi; Julyantoro, Pande Gde Sasmita; Wijayanti, Ni Putu Putri (Advances in Tropical Biodiversity and Environmental Sciences; Vol 4 No 1 (2020): ATBESDO - 10.24843/ATBES.2020.v04.i01.p02, 2020)
Addition of different fertilizer concentrations into cultivation media affects the cell density of microalgae. Potassium nitrate (KNO 3 ), is one of the components in Guillard fertilizer composition commonly used for microalgae culture. This study aims to determine the quality of Chaetoceros calcitrans when cultured with different concentration of KNO 3 . This research was conducted from November 2019 to January 2020 at Balai Perikanan Budidaya Air Payau (BPBAP) Situbondo and Biosain Laboratory, Jember State Politeknik, East Java. This study consists of four treatments and three replicates. The object in this study was C. calcitrans culture with initial density 10 5 cells/ml. The main parameters observed were cell density, biomass, protein and amino acids contents and medium parameters such as temperature, pH, DO, salinity, nitrate and phosphate. There were four concentrations of KNO 3 used in this study, namely control (75 g/l), treatment Group A (100 g/l), treatment B (125 g/l) and treatment C (150 g/l). The results showed that the cells density of C. calcitrans at control, treatment Group A, B and C were 110.4; 105.2; 108.3; and 100.8 (×10 4 cells/ml), respectively. This study indicated that different concentration of KNO 3 affect the starting point of stationary phase, but One Way ANOVA test showed that those treatments had no significant effect ( P ?0,05) on the growth rate and dry biomass of C. calcitrans . Finally, we found that the protein content in addition of 75, 100, 125 and 150 g/l KNO 3 were 9.748; 8.802; 6.812; and 3.776%, respectively.